Menafsir Ulang Kekristenan: Studi Atas Pandangan Keagamaan Tokoh-Tokoh pada Novel The Da Vinci Code - Ifa Nur Rofiqoh (Refleksi: Jurnal Kajian Agama dan Filsafat, 2016)
This article elucidates the Da Vinci Code (DVC) by Dan Brown. DVC became one of the most phenomenal novel with the best selling in the world and became the subject of discussion amongits readers, including Christians scholars.Dealing with the novel, there are three groups to response. First, the opinion believes that Jesus was just an ordinary man who descends from ‘Merovongian dynasti’ of Mary Magdalena, as the Holy Grail, and that opinion does not disseminate the belief. Second, as well as the first view, but this second group wants to spread the belief to the wider society. Third, the mainstream view that believes the crucifixtion of Jesus as the foundation of the Christian faith. Therefore, Jesus is a man and a God totally.